Study of Electrical and Optical Peaking of Si Ring Modulators for Tailoring Modulation Band - Hsiang-Chih Kao; Ming-Wei Lin; Ming-Chang M. Lee (IEEE Photonics Journal)
An operation scheme using electrical peaking and optical peaking to engineer the modulation band of a Si microring modulator is presented. By incorporating an inductor design at the metal traces of a Si microring modulator, the driving signal can be magnified near the peaking frequency. Although adjusting the wavelength detuning of a ring modulator also introduces optical peaking to extend the 3-dB roll-off frequency, using inductive peaking has no detrimental effect on the low-frequency response. By exploiting both effects, the modulation band can be tailored with more degrees of freedom. We accomplish a Si microring modulator design with a wide and flat transmission band over 95 GHz, which is potentially applied for a non-return-to-zero (NRZ) data transmission over 120 Gbit/s without extra signal post-compensation.